Size of offer, over-subscription ratio and performance of Malaysian IPOs - Yong, Othman; Yatim, Puan; Sapian, Ros Zam Zam (Universiti Utara Malaysia, 2002)
This paper examines the initial and the long-run performance of initial public offerings (IPOs) of stocks listed on the Main Board of the Kuala Lumpur Stock Exchange. This study finds a significant mean initial return and mean over-subscription ratio, even-though not as high as reported in earlier studies. Size of offer is not correlated with the over-subscription ratio. In general, initial returns are significantly higher than returns for subsequent longer-term holding periods. Mean initial returns among the three types of issue compared are not significantly different from each other: Only in the case of offer for sale that we find a significant positive correlation between its over-subscription ratio and its initial return. Offer-for sale also shows a positive correlation between its over-subscription ratio and its raw return for day-365, but turns significantly negative for day-910 and day-1095. In the case of combination of public issue and offer for sale, over-subscription ratio is not significantly correlated with longer term returns, for either raw or adjusted return. Finally, in the case of public issue, its over-subscription ratio is significantly correlated with its raw return only for day-180 and day-540, and for its adjusted return, the correlation is significant only for day-180 and day-365.